A Simple Algorithm for the Portfolio Selection Problem - Lewis, Alan L. (Journal of Finance, 1988)
The author presents a rapidly convergent algorithm to solve the general portfolio problem of maximizing concave utility functions subject to linear constraints. The algorithm is based on an iterative use of the Markowitz critical line method for solving quadratic programs. A simple example, taken from the theory of state-contingent claims, is worked out in detail. For technical convergence results, the reader is referred to the appropriate mathematical programming literature.